Frequency of the LRRK2 G2019S mutation in late-onset sporadic patients with Parkinson’s disease - Hsin Fen Chien; Tamires Rocha Figueiredo; Marianna Almeida Hollaender; Fabiano Tofoli; Leonel Takao Takada; Lygia da Veiga Pereira; Egberto Reis Barbosa (Arquivos de Neuro-Psiquiatria)
Mutations in the LRRK2 gene, predominantly G2019S, have been reported in individuals with autosomal dominant inheritance and sporadic Parkinson’s disease (PD). The G2019S mutation has an age-dependent penetrance and evidence shows common ancestry. The clinical manifestations are indistinguishable from idiopathic PD. Its prevalence varies according to the population studied ranging from less than 0.1% in Asians to 41% in North African Arabs. This study aimed to identify G2019S mutation in Brazilian idiopathic PD patients. Method: We sampled 100 PD patients and 100 age- and gender-matched controls. Genetical analysis was accomplished by polymerase chain reaction (PCR). Results: No G2019S mutations were found in both patients with sporadic PD and controls. Conclusions: Our results may be explained by the relatively small sample size.